Post-mortem magnetic resonance (PMMR) imaging of the brain in fetuses and children with histopathological correlation. Issue 12 (December 2017) - Shelmerdine, S.C.; Hutchinson, J.C.; Sebire, N.J.; Jacques, T.S.; Arthurs, O.J.
Abstract : Post-mortem magnetic resonance (PMMR) imaging is rapidly emerging as an alternative, "less invasive", and more widely accepted investigative approach for perinatal deaths in the UK. PMMR has a high diagnostic accuracy for congenital and acquired fetal neuropathological anomalies compared to conventional autopsy, and is particularly useful when autopsy is non-diagnostic. The main objectives of this review are to describe and illustrate the range of common normal and abnormal central nervous system (CNS) findings encountered during PMMR investigation. This article covers the standard PMMR sequences used at our institution, normal physiological post-mortem findings, and a range of abnormal developmental and acquired conditions. The abnormal findings include diseases ranging from neural tube defects, posterior fossa malformations, those of forebrain and commissural development as well as neoplastic, haemorrhagic, and infectious aetiologies. Neuropathological findings at conventional autopsy accompany many of the conditions we describe, allowing readers to better understand the underlying disease processes and imaging appearances.